A simple, high‐throughput and validated LC–MS/MS method for the determination of azithromycin in human plasma and its application to a clinical pharmacokinetic study. (19th July 2022) - Zhang, Yuning; Bala, Veenu; Chhonker, Yashpal S.; Aldhafiri, Wafaa N.; John, Lucy N.; Bjerum, Catherine M.; King, Christopher L.; Mitja, Oriol; Marks, Michael; Murry, Daryl J.
Abstract: A sensitive, specific and rapid liquid chromatographic–tandem mass spectrometric (LC–MS/MS) method was developed and validated to quantify azithromycin concentrations in human plasma. Azithromycin (AZI) is the most common outpatient prescribed antibiotic in the US and clinical studies have demonstrated the efficacy and safety of AZI in many bacterial infections. To support a clinical study, we developed a high‐throughput LC–MS/MS method to process up to 250 samples per day to quantify AZI in human plasma. Samples were prepared by solid‐phase extraction. Separation was achieved with an ACE C18 column (2.1 × 100 mm, 1.7 μm) equipped with a C18 guard column. The mobile phase consisted of 0.1% formic acid and methanol–acetonitrile (1:1, v/v) at a flow rate of 0.25 ml/min. The ionization was optimized with positive electrospray source using multiple reaction monitoring transition, m/z 749.50 > 591.45 for AZI and m/z 754.50 > 596.45 for AZI‐d5. Extraction recoveries were approximately 90% for AZI. The assay was linear from 0.5 to 2, 000 ng/ml and required only 100 μl of plasma with a total analysis time of 4.5 min. The method was successfully applied to pharmacokinetic studies of a weight‐based dosing protocol for AZI.